Features of physical and sexual development in school-aged children with psychosomatic disorders - I.S. Lebets; S.I. Turchina; T.M. Matkovska; S.V. Novokhatska; V.V. Nikonova; T.O. Kostenko; O.V. Shushlyapina (Zaslavsky O.Yu., 2021)
Background. Monitoring of physical and sexual development indicators using standards appropriate to age and sex, especially in children with chronic diseases is the most important element of management of children and adolescents with various pathologies because it allows managing the treatment process and improving it timely. Unfortunately, these issues have not been studied enough today. The purpose of the work is to determine the influence of somatic and mental diseases on the physical and sexual development impairments in school-age children. Materials and methods. Nine hundred and thirty-five patients aged 10-17 years (boys - 441, girls - 494) with the following pathology were examined: diabetes mellitus type 1, diffuse nontoxic goiter (DNG) with various menstrual disorders (girls with abnormal uterine bleeding), and girls with hypomenorrhea syndrome (HMS), mental disorders (functional and organic), systemic connective tissue dysplasia, secondary cardiomyopathy, juvenile idiopathic arthritis (JIA), systemic lupus erythematosus (SLE). The comparison group enrolled healthy children of the same age. Results. The presence of type 1 diabetes mellitus, diffuse nontoxic goiter were proved to negatively affect the somatosexual development of school-age children and contribute to the formation of disharmonious physical development (in 32.4 % of patients with diabetes mellitus 1 and 56.6 % of adolescents with DNG) and sexual maturation. It was established that 52.4 % of girls with gynecological pathology presented with harmonious physical development. Against the background of disharmony of physical development, girls are more likely to develop menstrual irregularities such as HMS. Harmonious physical development is registered in 50.8 % of patients with JIA. 67.25 % of people with JIA have normal growth rates. Exceedance of normal and lower values are observed in girls (p < 0.05). At the stages of puberty, the most common deviations in growth and body weight were observed in early puberty (100 %), the least often - in late puberty (42.8 %). In 56.8 % of patients with SLE, harmonious physical development was registered. The most common were as follows: overweight (33.3 %), decreased growth rate (17.6 %), and weight deficit (11.7 %). Based on the frequency of SLE, it was determined that the most vulnerable were puberty (91.0 %) and prepuberty (87.5 %). The onset of SLE in late puberty occurred in 26.3 % of cases. In patients with secondary cardiomyopathies and systemic connective tissue dysplasia, no significant statistical differences in age-related parameters were found. Most patients with mental disorders had a harmonious physical development (93.6 %). Among the violations of the latter, the deficit of body weight was most often determined (19.5 %).